Composition and application thereof
A polyhydroxy polymer composition addresses the instability and impurity issues of gelatin-based nano-twinned copper electroplating, resulting in a stable and high-quality nano-twinned copper layer with enhanced mechanical properties and reliability.
Patent Information
- Application Number
- CN202310809811.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
The use of gelatin as a promoter for nano-twinned copper electroplating is unstable and introduces impurities, making it difficult to control quality and leading to aging issues in semiconductor IC manufacturing.
A composition using a polyhydroxy polymer, derived from epoxy quaternary ammonium salt and 2,3-epoxypropanol, is used to induce the formation of nano-twinned copper with high strength and conductivity, providing a stable source and avoiding impurities.
The polyhydroxy polymer enables the production of a nano-twinned copper layer with improved mechanical properties and interconnection reliability, enhancing the quality and stability of electroplating solutions.
Smart Images

Figure CN119221051A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of electroplating metals, and in particular to a composition and its application. Background Art
[0002] As packaging technology develops towards increasing the density of package interconnects and continuously reducing the width of interconnects, higher requirements are placed on the performance of interconnect materials. The special structure of nano-twin materials gives them high ductility and tensile strength, and the twin boundaries have a weak ability to disperse electrons, and the resistance does not increase with the increase of grain boundaries. Therefore, nano-twin copper materials with both high strength and high conductivity are ideal candidates for the next generation of interconnect materials.
[0003] However, the main method for preparing nano-twinned copper is electroplating. The key to preparing nano-twinned copper by electroplating is to use additives to induce the growth of nano-twinned copper. The traditional additive for inducing the growth of nano-twinned copper is gelatin. Gelatin is a biopolymer material, and its main source is organisms. The source is unstable. For the manufacturing of delicate and complex ICs, materials with unstable sources are very difficult to control in quality. Therefore, gelatin, a traditional nano-twinned promoter, is difficult to be directly used in semiconductor IC manufacturing. In addition, gelatin contains various hydrolyzed proteins of unknown origin, which introduces a large number of impurity sources into the plating solution. The inclusion of large molecular proteins will cause the quality of the coating to drop sharply, and the plating solution is also prone to aging. Summary of the invention
[0004] In view of this, an embodiment of the present application provides a composition, which uses a polyhydroxy polymer as a nanotwin promoter. The composition can be used to prepare a metal interconnect structure by electroplating to obtain a nanotwin copper material with high strength and high conductivity, thereby helping to improve interconnection reliability and the yield of electronic products.
[0005] A first aspect of an embodiment of the present application provides a composition, which includes a metal ion source and a polyhydroxy polymer, wherein the polyhydroxy polymer is polymerized from monomer raw materials including an epoxy quaternary ammonium salt and 2,3-epoxypropanol.
[0006] The above-mentioned composition provided in the embodiment of the present application is an electroplating composition, which can be used to prepare a metal layer by electroplating to form a metal interconnection structure, wherein the polyhydroxy polymer as a nanotwin promoter can induce the formation of a high-density columnar nanotwin copper material with a high preferred (111) crystal plane orientation, and make the nanotwin copper layer prepared by electroplating have a transition layer with an extremely low thickness, thereby greatly improving the mechanical properties of the metal copper layer and improving the interconnection reliability; and the source of the polyhydroxy polymer material is stable, and no impurities that affect the plating solution performance and the quality of the plating layer will be introduced into the plating solution. The polyhydroxy polymer of the embodiment of the present application is obtained by a hyperbranched polymerization reaction and is a hyperbranched polyhydroxy polymer. Specifically, the polyhydroxy polymer is prepared by hyperbranched polymerization of monomer raw materials including epoxy quaternary ammonium salt and 2,3-epoxypropanol. The nitrogen content in the molecular structure of the polyhydroxy polymer can be adjusted by regulating the feed ratio of epoxy quaternary ammonium salt and 2,3-epoxypropanol during the preparation process. The nitrogen content of the polyhydroxy polymer directly affects the performance of the nano-twin structure. Therefore, the hyperbranched polyhydroxy polymer of the embodiment of the present application can be used to regulate the lamellar density of the nano-twin copper layer by adjusting the nitrogen content, thereby regulating the mechanical properties of the nano-twin copper layer.
[0007] Among them, the structural formula of 2,3-epoxypropanol is: Epoxy quaternary ammonium salt is a new type of quaternary ammonium salt that introduces epoxy groups on the basis of ordinary quaternary ammonium salt. Epoxy quaternary ammonium salt contains active epoxy groups in its molecules and is easy to react with other polymer materials.
[0008] In the embodiment of the present application, the epoxy quaternary ammonium salt has the general structural formula shown in formula (1):
[0009]
[0010] In formula (1), n is an integer of 0≤n≤5, R1, R2 and R3 are independently selected from substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted n-propyl, substituted or unsubstituted isopropyl or derivatives thereof, and R4 is selected from H, substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted n-propyl, substituted or unsubstituted isopropyl or derivatives thereof. R1, R2, R3 and R4 have a small number of carbon atoms, which can make the epoxy quaternary ammonium salt molecule less hindered, which is conducive to the hyperbranching reaction.
[0011] In the present application embodiment, the epoxy quaternary ammonium salt includes trimethyl glycidyl quaternary ammonium salt, 3,4-epoxybutyl trimethyl quaternary ammonium salt, 4,5-epoxypentyl trimethyl quaternary ammonium salt, epoxyethyl triethyl quaternary ammonium salt, 2,3-epoxypropyl triethyl quaternary ammonium salt, 1,1-bis (epoxypropyl) dimethyl quaternary ammonium salt, 2-methyl glycidyl trimethyl quaternary ammonium salt, 2-ethyl glycidyl trimethyl quaternary ammonium salt, 2-propyl glycidyl trimethyl quaternary ammonium salt, 2-methyl glycidyl trimethyl quaternary ammonium salt, 2-methyl glycidyl trimethyl quaternary ammonium salt, 2-methyl glycidyl triethyl quaternary ammonium salt. One or more of the above-mentioned epoxy quaternary ammonium salt can smoothly realize hyperbranched reaction with 2,3-epoxypropanol under simpler reaction conditions, and prepare a hyperbranched polyhydroxy polymer with controllable nitrogen content and controllable molecular weight, and the above-mentioned epoxy quaternary ammonium salt raw material is easy to obtain.
[0012] In the embodiment of the present application, the polyhydroxy polymer is polymerized by the 2,3-epoxypropanol and the epoxy quaternary ammonium salt at a reaction feed ratio of less than or equal to 500: 1. A suitable reaction feed ratio of 2,3-epoxypropanol to epoxy quaternary ammonium salt can better regulate the nitrogen content in the polyhydroxy polymer, thereby better obtaining a nano twinned copper layer with a lower transition layer and a high twin density.
[0013] In the embodiment of the present application, the molecular weight of the polyhydroxy polymer is 500 g / mol-50000 g / mol. A suitable molecular weight can make the polyhydroxy polymer disperse better in the composition and make the viscosity of the whole composition within a suitable range.
[0014] In the embodiment of the present application, in the composition, the concentration of the polyhydroxy polymer is 0.01ppm-5000ppm. Controlling the concentration of the polyhydroxy polymer within a suitable range is conducive to promoting the formation of nano-twinned copper, while effectively avoiding the adverse effects that may be caused by excessive addition of the polyhydroxy polymer.
[0015] In an embodiment of the present application, the metal ion source includes any one of a copper ion source, a nickel ion source, a tin ion source, a cobalt ion source, a ruthenium ion source, and a silver ion source. The metal ion source may be a soluble metal salt, wherein the copper ion source is a soluble copper salt. In some embodiments of the present application, the copper ion source includes one or more of copper sulfate pentahydrate and copper methanesulfonate. In some embodiments of the present application, the concentration of the copper ion source in the composition is 1g / L-300g / L in terms of copper ions. Controlling the copper ion source within a suitable content range is beneficial to taking into account the deposition rate and the brightness and flatness of the resulting copper coating.
[0016] In the embodiment of the present application, the composition further comprises at least one acid. In some embodiments of the present application, the at least one acid comprises one or more of sulfuric acid and methanesulfonic acid. In some embodiments of the present application, the concentration of the at least one acid in the composition is 1g / L-300g / L. Suitable acid systems and acid concentrations are conducive to obtaining suitable electroplating deposition rates.
[0017] In the embodiment of the present application, the composition further comprises one or more of an accelerator, an inhibitor, a leveler, and an inorganic additive. The polyhydroxy polymer cooperates with one or more of an accelerator, an inhibitor, a leveler, and an inorganic additive to better realize the electroplating preparation of metal layers on electronic substrates of different scenarios, different structural sizes, and different requirements.
[0018] In the embodiment of the present application, the inorganic additive may include chloride ions, and the concentration of chloride ions in the composition is 0.1ppm-100ppm. The addition of chloride ions can improve the crystal density of the coating and make the coating finer and less rough.
[0019] In the embodiment of the present application, the leveling agent may be a copolymer of ether and nitrogen-containing compound. Using the copolymer of ether and nitrogen-containing compound as the leveling agent can effectively inhibit metal deposition in the area corresponding to the high current density and improve the uniformity of the metal coating.
[0020] In some embodiments of the present application, the concentration of the leveler in the composition is 0.01-100 ppm. Controlling the concentration of the leveler in the composition within a suitable range is conducive to obtaining a moderate deposition rate, improving the uniformity and flatness of the electroplating of the entire electronic substrate, thereby facilitating the production of fine circuits and improving the reliability of electronic products.
[0021] In the embodiments of the present application, the accelerator may be one or more of 3-mercapto-1-propane sulfonate sodium (MPS), polydisulfide propane sulfonate sodium (SPS) and N,N-dimethyl-dithiocarboxamide propane sulfonate sodium (DPS). In some embodiments of the present application, the concentration of the accelerator in the composition is 0.01ppm-500ppm. The accelerator includes: the concentration of the accelerator in the electroplating composition is 0.01ppm-500ppm. The addition of the accelerator can play a role in depolarization, accelerate the deposition of the metal, and refine the grains of the metal layer.
[0022] In the embodiments of the present application, the inhibitor may be one or more of polyethylene glycol (PEG), polypropylene glycol (PPG), block copolymer PEO-PPO-PEO, block copolymer PPO-PEO-PPO, random copolymer of EO and PO, and propylene glycol block polyether. In some embodiments of the present application, the concentration of the inhibitor in the composition is 1ppm-2000ppm. The addition of the inhibitor can inhibit the growth rate of the surface metal, which is conducive to obtaining a thinner surface metal layer after the electroplating is completed.
[0023] In the embodiment of the present application, the nano-twinned copper layer prepared by electroplating the composition has a (111) crystal plane orientation. The grains of the nano-twinned copper layer have a (111) crystal plane orientation, which is conducive to obtaining a nano-twinned copper layer with relatively regular crystallization, improving the compactness of the nano-twinned copper layer, and further improving the mechanical properties of the nano-twinned copper layer.
[0024] In the embodiment of the present application, the tensile strength of the nano-twinned copper layer prepared by electroplating the composition is increased by 20% or more compared to the ordinary copper layer, and the ductility is increased by 30% or more compared to the ordinary copper layer; wherein the ordinary copper layer is prepared under the same conditions by a plating solution without adding the polyhydroxy polymer compared to the composition. The nano-twinned copper layer has high tensile strength and ductility, which is beneficial to reduce the failure risk of it as an interconnection structure and improve the reliability of interconnection.
[0025] In the embodiment of the present application, the transition layer thickness of the nano twinned copper layer prepared by electroplating the composition is less than or equal to 1 μm. A smaller transition layer thickness is conducive to obtaining a more uniform overall film layer with better overall film performance.
[0026] In the implementation manner of the present application, a dimple section exists in the tensile section of the nano-twin copper layer prepared by electroplating the composition. A dimple section refers to a section of a dimple fracture (microporous aggregation fracture) covered with a large number of microscopic pits. These micropits (pits) are called "dimples". Dimples are the main microscopic features of plastic fracture of metals. It is a microscopic void produced by plastic deformation of the material within a micro-region, which is left on the section after nucleation, growth, aggregation and finally interconnection leading to fracture. The size of the dimple includes an average diameter and a depth. Generally, when the fracture conditions are the same, the larger the dimple size, the better the plasticity of the material. The presence of a dimple section in the tensile section of the nano-twin copper layer of the implementation manner of the present application indicates that the nano-twin copper layer has good plasticity.
[0027] The second aspect of the embodiment of the present application provides the use of the composition described in the first aspect in preparing a metal layer by electroplating. The composition described in the first aspect of the embodiment of the present application can be used to prepare a dense nano-twinned copper layer with a high preferred (111) crystal plane orientation by electroplating, and the thickness of the transition layer is small, thereby greatly improving the mechanical properties and interconnection quality of the metal copper layer and improving the interconnection reliability.
[0028] In the embodiment of the present application, the metal layer includes any one of a copper layer, a copper alloy layer, a nickel layer, a nickel alloy layer, a tin layer, a tin alloy layer, a cobalt layer, a cobalt alloy layer, a ruthenium layer, a ruthenium alloy layer, a silver layer, and a silver alloy layer. The composition described in the first aspect of the embodiment of the present application is applied to the electroplating preparation of the metal interconnect structure of the advanced packaging to improve the interconnect reliability.
[0029] In the embodiment of the present application, the electroplating preparation of the metal layer includes electroplating the metal layer in the conductive hole on the electronic substrate to achieve metal filling. The electroplating preparation of the metal layer can also be electroplating preparation of the metal layer on an electronic substrate of other structures.
[0030] The third aspect of the embodiment of the present application provides a polyhydroxy polymer for preparing a metal layer by electroplating, wherein the polyhydroxy polymer is polymerized from monomer raw materials including epoxy quaternary ammonium salt and 2,3-epoxypropanol. The polyhydroxy polymer can be used as a nanotwin promoter to induce the generation of a high-density columnar nanotwin copper material with a high preferred (111) crystal plane orientation, and the nanotwin copper layer prepared by electroplating has a transition layer with an extremely low thickness, thereby greatly improving the mechanical properties of the metal copper layer and improving the interconnection reliability; and the polyhydroxy polymer material source is stable, and impurities that affect the performance of the plating solution and the quality of the coating will not be introduced into the plating solution; in addition, the polyhydroxy polymer can adjust the nitrogen content in the molecular structure of the polyhydroxy polymer by adjusting the feed ratio of epoxy quaternary ammonium salt and 2,3-epoxypropanol during the preparation process; and then adjust the sheet density of the nanotwin copper layer, thereby adjusting the mechanical properties of the nanotwin copper layer to meet the needs of different scenarios.
[0031] In the embodiment of the present application, the epoxy quaternary ammonium salt has the general structural formula shown in formula (1):
[0032]
[0033] In formula (1), n is an integer of 0≤n≤5, R1, R2 and R3 are independently selected from substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted n-propyl, substituted or unsubstituted isopropyl or derivatives thereof, and R4 is selected from H, substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted n-propyl, substituted or unsubstituted isopropyl or derivatives thereof. R1, R2, R3 and R4 have a small number of carbon atoms, which can make the epoxy quaternary ammonium salt molecule less hindered, which is conducive to the hyperbranching reaction.
[0034] In the present application embodiment, the epoxy quaternary ammonium salt includes trimethyl glycidyl quaternary ammonium salt, 3,4-epoxybutyl trimethyl quaternary ammonium salt, 4,5-epoxypentyl trimethyl quaternary ammonium salt, epoxyethyl triethyl quaternary ammonium salt, 2,3-epoxypropyl triethyl quaternary ammonium salt, 1,1-bis (epoxypropyl) dimethyl quaternary ammonium salt, 2-methyl glycidyl trimethyl quaternary ammonium salt, 2-ethyl glycidyl trimethyl quaternary ammonium salt, 2-propyl glycidyl trimethyl quaternary ammonium salt, 2-methyl glycidyl trimethyl quaternary ammonium salt, 2-methyl glycidyl trimethyl quaternary ammonium salt, 2-methyl glycidyl triethyl quaternary ammonium salt. One or more of the above-mentioned epoxy quaternary ammonium salt can smoothly realize hyperbranched reaction with 2,3-epoxypropanol under simpler reaction conditions, and prepare a hyperbranched polyhydroxy polymer with controllable nitrogen content and controllable molecular weight, and the above-mentioned epoxy quaternary ammonium salt raw material is easy to obtain.
[0035] A fourth aspect of the present application provides a method for preparing a metal layer by electroplating, comprising the following steps:
[0036] The substrate to be electroplated is contacted with the composition described in the first aspect of the embodiment of the present application, and current is applied to the substrate to be electroplated for electroplating, so that a metal layer is formed on the substrate to be electroplated.
[0037] The method for preparing a metal layer by electroplating in the embodiment of the present application has a simple process and is easy to control.
[0038] In some embodiments of the present application, the substrate to be plated is provided with a via hole, and the metal layer includes an in-hole filling layer filling the via hole and a surface deposition layer deposited around the via hole.
[0039] In some embodiments of the present application, the electroplating process conditions are: electroplating temperature is 22° C.-45° C., current density is 0.1ASD-15ASD, and electroplating time is 30min-300min. Under such process conditions, it is beneficial to obtain a high-quality metal layer by electroplating.
[0040] The fifth aspect of the embodiment of the present application provides an electronic substrate, including a base layer and a metal layer arranged on the base layer, wherein the metal layer is formed by electroplating the composition described in the first aspect, or by the method for preparing the metal layer by electroplating described in the fourth aspect. The electronic substrate of the embodiment of the present application can be various substrates that require electroplating to prepare the metal layer, which can be an amorphous substrate or a polycrystalline substrate, and the structural size, shape, etc. of the electronic substrate are not particularly limited. The electronic substrate can be, for example, a silicon substrate, a compound semiconductor substrate, or an organic substrate. The above-mentioned composition of the present application can be electroplated to obtain a dense nano-twinned copper layer with a high preferred (111) crystal plane orientation, and the thickness of the transition layer is small, thereby greatly improving the mechanical properties and interconnection quality of the metal copper layer, and improving the interconnection reliability. Nano-twinned copper has high strength and high conductivity, and improves the interconnection reliability and performance in advanced packaging metal interconnection technologies such as ultra-fine RDL (ReDistribution Layer) and hybrid bonding.
[0041] The embodiment of the present application further provides an electronic device, wherein the electronic device adopts the electronic substrate described in the fifth aspect of the embodiment of the present application. The electronic device may be a chip, a transistor, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 A schematic diagram of copper electroplating provided in an embodiment of the present application;
[0043] Figure 2 A schematic diagram of the structure of an electronic substrate 100 provided in an embodiment of the present application;
[0044] Figure 3 This is the nuclear magnetic resonance spectrum of the polyhydroxy polymer prepared in Example 1 of the present application;
[0045] Figure 4 This is a cross-sectional SEM (Scanning Electron Microscope) image of the nano-twinned copper layer prepared in Example 1;
[0046] Figure 5 The XRD (X-ray diffraction) spectrum of the nano-twinned copper layer prepared in Example 1;
[0047] Figure 6 The EBSD (Electron Backscattered Diffraction) spectrum of the nano-twinned copper layer prepared in Example 1;
[0048] Figure 7 This is a SEM image of the tensile cross section of the nano-twinned copper layer prepared in Example 1;
[0049] Figure 8 This is a cross-sectional SEM image of the nano-twinned copper layer prepared in Comparative Example 1;
[0050] Fig. 9 This is a SEM image of a tensile cross section of a common polycrystalline copper layer prepared in Comparative Example 2;
[0051] Fig.10 is a cross-sectional SEM image of the nano-twinned copper layer of Example 2;
[0052] Fig.11 is a SEM image of a cross section of the nano-twinned copper layer of Example 3;
[0053] Fig.12 This is a SEM image of the cross section of the nanotwinned copper layer of Example 4. DETAILED DESCRIPTION
[0054] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.
[0055] As packaging technology develops towards the direction of increasing the density of package interconnects and continuously reducing the width of interconnects, higher requirements are placed on the performance of interconnect materials. On the one hand, due to the increase in interconnect density, heat generation increases, the thermal expansion coefficients of copper wires and silicon do not match, and there is a risk of interconnects breaking; on the other hand, as the width of interconnects continues to decrease, the current carried by the interconnects increases, which also brings potential failure risks. The special structure of nanotwin materials gives them high ductility and tensile strength, and the twin boundaries have weak dispersion capabilities for electrons. Although the grain boundaries increase, the resistance does not increase accordingly. Therefore, nanotwin copper materials with both high strength and high conductivity are ideal candidates for the next generation of interconnect materials.
[0056] However, the main method for preparing nano-twinned copper is electroplating. Electroplating is a method of reducing metal ions to metals by electrochemical methods and depositing them on the surface of metal or non-metal products to form a smooth and dense metal coating that meets the requirements. Electroplating uses a conductive substrate as the cathode, on whose surface a metal deposition reduction reaction occurs (the cathode is an electrode that receives electrons, that is, an electrode that undergoes a reduction reaction), and a soluble or insoluble anode to cause metal dissolution or oxygen evolution (the anode is an electrode that can cause an oxidation reaction in the electrolyte), with the plating solution as the conductive circuit of the electrolyte. Figure 1 As shown, Figure 1 The schematic diagram of copper electroplating. In the copper electroplating technology in the packaging field, the cathode plated part is the substrate to be electroplated. Through the metal deposition reaction of the cathode, the conductive metal copper is deposited into the required interconnection structure.
[0057] The key to preparing nano-twinned copper by electroplating is to use additives to induce the growth of nano-twinned copper. The traditional additive for inducing the growth of nano-twinned copper is gelatin. Gelatin is a biopolymer material, and its main source is organisms. The source is unstable. For the manufacturing of delicate and complex ICs, materials with unstable sources are very difficult to control in quality. Therefore, gelatin, a traditional nano-twinned promoter, is difficult to be directly used in semiconductor IC manufacturing. In addition, gelatin contains various hydrolyzed proteins of unknown origin, which introduces a large number of impurity sources into the plating solution. The inclusion of large molecular proteins will cause the quality of the coating to drop sharply, and the plating solution is also prone to aging.
[0058] In order to solve the above problems, the present application embodiment provides a polyhydroxy polymer, and a composition comprising the polyhydroxy polymer. The polyhydroxy polymer provided in the present application embodiment is polymerized from monomer raw materials including epoxy quaternary ammonium salt and 2,3-epoxypropanol. That is, the polyhydroxy polymer simultaneously includes structures derived from epoxy quaternary ammonium salt and 2,3-epoxypropanol. The polyhydroxy polymer can be used as a nano-twin promoter. The composition containing the polyhydroxy polymer is used as an electroplating solution for electroplating to prepare a metal layer. The specific adsorption of the polyhydroxy polymer can induce the generation of a high-density columnar nano-twin copper material with a high preferred (111) crystal plane orientation, and the nano-twin copper layer prepared by electroplating has a transition layer with an extremely low thickness, thereby greatly improving the mechanical properties and plating quality of the metal copper layer, so that the metal copper layer has both high strength and high conductivity, and improves the interconnection reliability; and the source of the polyhydroxy polymer material is stable, and no impurities that affect the plating solution performance and the plating quality will be introduced into the plating solution; in addition, the polyhydroxy polymer can adjust the nitrogen content in the molecular structure of the polyhydroxy polymer by adjusting the feed ratio of epoxy quaternary ammonium salt and 2,3-epoxypropanol during the preparation process, and the molecular weight can also be adjusted; and the transition layer thickness and the nano-twin copper layer sheet density can be adjusted, which is conducive to obtaining a nano-twin copper layer with a lower transition layer thickness and a higher twin density, thereby adjusting the mechanical properties of the nano-twin copper layer to meet the needs of different scenarios.
[0059] In the present application, the terms "composition", "electroplating composition", "plating solution", and "electroplating solution" can be used interchangeably. The terms "copper layer", "metal layer", "metal copper layer", "nano-twinned copper layer", "plating layer", and "copper plating layer" can be used interchangeably.
[0060] Among them, the structural formula of 2,3-epoxypropanol is: Epoxy quaternary ammonium salt is a new type of quaternary ammonium salt that introduces epoxy groups on the basis of ordinary quaternary ammonium salt. Epoxy quaternary ammonium salt contains active epoxy groups in the molecule and is easy to react with other polymer materials. Compared with non-epoxy amine alcohols or ammonium alcohols that use hydroxyl groups to initiate the epoxy ring opening of 2,3-epoxy propanol, the polyhydroxy compound of the present application undergoes hyperbranched anionic polymerization reaction between epoxy quaternary ammonium salt and 1,2-epoxy propanol. The reaction can simultaneously regulate the nitrogen content and molecular weight of the compound, thereby regulating the sheet density of the nano twin copper layer.
[0061] In the embodiment of the present application, the epoxy quaternary ammonium salt has the general structural formula shown in formula (1):
[0062]
[0063] In formula (1), n is an integer of 0≤n≤5, R1, R2 and R3 are independently selected from substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted n-propyl, substituted or unsubstituted isopropyl or derivatives thereof, and R4 is selected from H, substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted n-propyl, substituted or unsubstituted isopropyl or derivatives thereof. R1, R2, R3 and R4 have a small number of carbon atoms, which can make the epoxy quaternary ammonium salt molecule less hindered, which is conducive to the hyperbranching reaction.
[0064] In formula (1), n can specifically be 0, 1, 2, 3, 4 or 5. When R1, R2, R3, and R4 are substituted methyl, substituted ethyl, substituted n-propyl, or substituted isopropyl, the substituent group may be a halogen atom, an alkyl group, or the like.
[0065] In some embodiments of the present application, epoxy quaternary ammonium salts may include, for example, trimethyl glycidyl quaternary ammonium salts, 3,4-epoxybutyl trimethyl quaternary ammonium salts, 4,5-epoxypentyl trimethyl quaternary ammonium salts, epoxyethyl triethyl quaternary ammonium salts, 2,3-epoxypropyl triethyl quaternary ammonium salts, 1,1-di(epoxypropyl) dimethyl quaternary ammonium salts, 2-methyl glycidyl trimethyl quaternary ammonium salts, 2-ethyl glycidyl trimethyl quaternary ammonium salts, 2-propyl glycidyl trimethyl quaternary ammonium salts, 2-methyl glycidyl trimethyl quaternary ammonium salts, and one or more of 2-methyl glycidyl trimethyl quaternary ammonium salts. The above-mentioned epoxy quaternary ammonium salts can smoothly realize hyperbranched reaction with 2,3-epoxypropanol under simpler reaction conditions, and prepare hyperbranched polyhydroxy polymers with controllable nitrogen content and controllable molecular weight, and the above-mentioned epoxy quaternary ammonium salt raw materials are easy to obtain.
[0066] In some embodiments of the present application, the polyhydroxy polymer is polymerized from one monomer raw material of epoxy quaternary ammonium salt and 2,3-epoxypropanol. In some embodiments of the present application, the polyhydroxy polymer is polymerized from multiple (two or more) monomer raw materials of epoxy quaternary ammonium salt and 2,3-epoxypropanol.
[0067] In some embodiments of the present application, the polyhydroxy polymer is polymerized by 2,3-epoxypropanol and epoxy quaternary ammonium salt at a reaction feed ratio of less than or equal to 500:1. In some embodiments, the reaction feed ratio of 2,3-epoxypropanol and epoxy quaternary ammonium salt can be 20-300:1. In some embodiments, the reaction feed ratio of 2,3-epoxypropanol and epoxy quaternary ammonium salt can be 50-200:1. In some embodiments, the reaction feed ratio of 2,3-epoxypropanol and epoxy quaternary ammonium salt can be 60-150:1. In some embodiments, the reaction feed ratio of 2,3-epoxypropanol and epoxy quaternary ammonium salt can be 80-120:1. A suitable reaction feed ratio of 2,3-epoxypropanol and epoxy quaternary ammonium salt can better regulate the nitrogen content in the polyhydroxy polymer, thereby better obtaining a nano-twinned copper layer with a lower transition layer and a high twin density.
[0068] In the embodiment of the present application, the molecular weight of the polyhydroxy polymer may be 500 g / mol-50000 g / mol. In some embodiments, the molecular weight of the polyhydroxy polymer may be, for example, 500 g / mol, 1000 g / mol, 2500 g / mol, 5000 g / mol, 10000 g / mol, 20000 g / mol, 30000 g / mol, 40000 g / mol, 50000 g / mol. Suitable molecular weight can obtain suitable adsorption strength on the copper surface during the formation of the coating, better induce twin production, form a better quality coating, and make the polyhydroxy polymer better dispersed in the composition, while making the overall viscosity of the composition within a suitable range.
[0069] The present application embodiment also provides a composition, which includes a metal ion source and the above-mentioned polyhydroxy polymer. The composition is an electroplating composition. The composition uses the above-mentioned polyhydroxy polymer as a nanotwin promoter, which can be used to electroplating to prepare a metal layer to form a metal interconnection structure, and obtain a nanotwin copper interconnection structure with high strength and high conductivity, which is beneficial to improve the interconnection reliability and yield of electronic products. Among them, the polyhydroxy polymer as a nanotwin promoter can be adsorbed on the copper surface through N atoms as the core adsorption center, and the hydroxyl groups in the molecules provide appropriate polarization, thereby inducing the formation of high-density columnar nanotwin copper materials with high preferential (111) crystal plane orientation, and the nanotwin copper layer prepared by electroplating has a transition layer with extremely low thickness, thereby greatly improving the mechanical properties of the metal copper layer and improving the interconnection reliability; and the source of the polyhydroxy polymer material is stable, and impurities that affect the performance of the plating solution and the quality of the coating will not be introduced into the plating solution. The polyhydroxy polymer of the embodiment of the present application is obtained by hyperbranched polymerization reaction, and is a hyperbranched polyhydroxy polymer. Specifically, the polyhydroxy polymer is formed by hyperbranched polymerization of monomer raw materials including epoxy quaternary ammonium salt and 2,3-epoxypropanol. The nitrogen content in the molecular structure of the polyhydroxy polymer can be adjusted by regulating the feed ratio of epoxy quaternary ammonium salt and 2,3-epoxypropanol during the preparation process. N exists as an adsorption center in the polyhydroxy polymer, and N has a strong adsorption force on the copper surface. The nitrogen content of the polyhydroxy polymer directly affects the performance of the nano-twin structure. Therefore, the hyperbranched polyhydroxy polymer of the embodiment of the present application can be used to regulate the lamellar density of the nano-twin copper layer by adjusting the nitrogen content, thereby regulating the mechanical properties of the nano-twin copper layer.
[0070] In the embodiment of the present application, in the above-mentioned composition, the concentration of the polyhydroxy polymer can be 0.01ppm-5000ppm. In some embodiments of the present application, the concentration of the polyhydroxy polymer in the composition is 0.1ppm-500ppm. In some embodiments of the present application, the concentration of the polyhydroxy polymer in the composition is 0.1ppm-100ppm. Exemplarily, the concentration of the polyhydroxy polymer in the composition can be 0.01ppm, 0.1ppm, 10ppm, 50ppm, 100ppm, 200ppm, 500ppm, 1000ppm, 2000ppm, 3000ppm, 4000ppm, 5000ppm. Controlling the concentration of the polyhydroxy polymer within a suitable range is conducive to promoting the formation of nano-twinned copper, while effectively avoiding the adverse effects that may be caused by excessive addition of the polyhydroxy polymer, such as excessive addition of the polyhydroxy polymer may cause the coating to be mixed with too many additives, thereby causing a high impurity content.
[0071] In the embodiments of the present application, the metal ion source includes any one of a copper ion source, a nickel ion source, a tin ion source, a cobalt ion source, a ruthenium ion source, and a silver ion source. The metal ion source may be a soluble metal salt, wherein the copper ion source is a soluble copper salt. In some embodiments of the present application, the copper ion source includes one or more of copper sulfate pentahydrate and copper methane sulfonate. For example, in some embodiments, the copper ion source includes copper sulfate pentahydrate; in some embodiments, the copper ion source includes copper methane sulfonate; in some embodiments, the copper ion source includes copper sulfate pentahydrate and copper methane sulfonate. Electroplating using the above-mentioned copper ion source acid system has high current efficiency, is environmentally friendly, and can better achieve blind hole filling through the combination of various additives.
[0072] In some embodiments of the present application, the concentration of the copper ion source in the composition is 1g / L-300g / L in terms of copper ions. In some embodiments of the present application, the concentration of the copper ion source in the composition can be 1g / L-120g / L in terms of copper ions. In some embodiments, the concentration of the copper ion source in the composition can be 1g / L, 10g / L, 20g / L, 30 / L, 40g / L, 50g / L, 60g / L, 70g / L, 80g / L, 90g / L, 100g / L, 110g / L, 120g / L in terms of copper ions. Controlling the copper ion source in a suitable content range is beneficial to taking into account the deposition rate and the brightness and flatness of the resulting copper coating.
[0073] In the embodiment of the present application, the composition also includes at least one acid. In some embodiments of the present application, the at least one acid includes one or more of sulfuric acid and methylsulfonic acid. In some embodiments of the present application, the concentration of the at least one acid in the composition can be 1g / L-300g / L. In some embodiments, the concentration of the at least one acid in the composition can be 1g / L, 10g / L, 20g / L, 30g / L, 40g / L, 50g / L, 55g / L, 60g / L, 70g / L, 80g / L, 100g / L, 120g / L, 150g / L, 180g / L, 200g / L, 220g / L, 250g / L, 300g / L. Suitable acid system and acid concentration are conducive to obtaining suitable electroplating deposition rate.
[0074] In the embodiment of the present application, the composition further comprises one or more of an accelerator, an inhibitor, a leveler, and an inorganic additive. The polyhydroxy polymer cooperates with one or more of an accelerator, an inhibitor, a leveler, and an inorganic additive to better realize the electroplating preparation of metal layers on electronic substrates of different scenarios, different structural sizes, and different requirements.
[0075] In the embodiment of the present application, the inorganic additive may include chloride ions, and the concentration of chloride ions in the composition may be 0.1ppm-100ppm. In some embodiments, in the composition, the concentration of chloride ions may be 0.1ppm, 1ppm, 5ppm, 10ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm. The addition of chloride ions can improve the crystal density of the coating and make the coating finer and less rough.
[0076] In the embodiment of the present application, the leveling agent may be a copolymer of ether and nitrogen-containing compound. Using the copolymer of ether and nitrogen-containing compound as the leveling agent can effectively inhibit metal deposition in the area corresponding to the high current density and improve the uniformity of the metal coating.
[0077] In some embodiments of the present application, the ether may be a symmetrical ether or an asymmetrical ether, may contain one ether oxygen bond or multiple ether oxygen bonds, may be an aliphatic ether or an aromatic ether; the nitrogen-containing compound may be substituted or unsubstituted pyrrole, substituted or unsubstituted pyrimidine, substituted or unsubstituted azole, substituted or unsubstituted thiazole, substituted or unsubstituted benzopyrrole, substituted or unsubstituted benzimidazole, substituted or unsubstituted benzopyridine, substituted or unsubstituted benzopyrimidine, substituted or unsubstituted benzotriazole, substituted or unsubstituted benzothiazole, substituted or unsubstituted bipyridine group, substituted or unsubstituted triazine, etc.
[0078] In some embodiments of the present application, the concentration of the leveler in the composition can be 0.01-100ppm. In some embodiments, the concentration of the leveler is 0.1ppm-80ppm; in some embodiments, the concentration of the leveler is 1ppm-50ppm. Exemplarily, the concentration of the leveler can be 0.01ppm, 0.1ppm, 1ppm, 2ppm, 5ppm, 8ppm, 10ppm, 12ppm, 15ppm, 18ppm, 20ppm, 25ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm. Controlling the concentration of the leveler in the composition within a suitable range is conducive to obtaining a moderate deposition rate, improving the uniformity and flatness of the entire electronic substrate electroplating, thereby facilitating the production of fine circuits and improving the reliability of electronic products.
[0079] In the embodiment of the present application, the accelerator may be one or more of 3-mercapto-1-propane sulfonate sodium (MPS), polydisulfide dipropane sulfonate sodium (SPS) and N, N-dimethyl-dithiocarboxamide propane sulfonate sodium (DPS). In some embodiments of the present application, the concentration of the accelerator in the composition is 0.01ppm-500ppm. In some embodiments of the present application, the concentration of the accelerator in the composition is 0.05ppm-20ppm. In some embodiments of the present application, the concentration of the accelerator in the composition is 0.1ppm-10ppm. Exemplarily, the concentration of the accelerator in the composition is 0.01ppm, 0.05ppm, 0.1ppm, 0.2ppm, 0.5ppm, 10ppm, 20ppm, 50ppm, 100ppm, 200ppm, 300ppm, 400ppm, 500ppm. The addition of the accelerator can play a role in accelerating the deposition of the metal by a depolarizing effect, as well as refining the grains of the metal layer.
[0080] In the embodiments of the present application, the inhibitor may be one or more of polyethylene glycol (PEG), polypropylene glycol (PPG), block copolymer PEO-PPO-PEO, block copolymer PPO-PEO-PPO, random copolymer of EO and PO, and propylene glycol block polyether. In some embodiments of the present application, the concentration of the inhibitor in the composition is 1ppm-2000ppm. In some embodiments of the present application, the concentration of the inhibitor in the composition is 10ppm-1000ppm. In some embodiments of the present application, the concentration of the inhibitor in the composition is 1ppm-10ppm. Exemplarily, the concentration of the accelerator in the composition is 1ppm, 10ppm, 20ppm, 50ppm, 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm. The addition of the inhibitor can inhibit the growth rate of the surface metal, which is conducive to obtaining a thinner surface metal layer after completing the electroplating.
[0081] It is understandable that other nanotwin promoters that can promote the formation of nanotwin copper can also be added to the composition, that is, used in combination with the polyhydroxy polymer of the embodiment of the present application.
[0082] In the embodiment of the present application, the nano-twinned copper layer prepared by electroplating the above composition has a (111) crystal plane orientation. The grains of the nano-twinned copper layer have a (111) crystal plane orientation, which is conducive to obtaining a nano-twinned copper layer with relatively regular crystallization, improving the compactness of the nano-twinned copper layer, and further improving the mechanical properties of the nano-twinned copper layer.
[0083] In the embodiment of the present application, the tensile strength of the nano twinned copper layer prepared by electroplating with the above composition is increased by greater than or equal to 20% compared with the ordinary copper layer, and the ductility is increased by greater than or equal to 30% compared with the ordinary copper layer; wherein the ordinary copper layer is prepared under the same conditions by a plating solution without adding a polyhydroxy polymer compared with the above composition of the present application. For example, the composition of the present application includes 200g / L of copper sulfate pentahydrate, 50g / L of sulfuric acid, 60ppm of chloride ion concentration, and 100ppm of polyhydroxy polymer; then the plating solution for preparing the ordinary copper layer only adds less polyhydroxy polymer than the composition of the present application, and the other components are exactly the same, and the electroplating process is also exactly the same. The nano twinned copper layer has high tensile strength and ductility, which is beneficial to reduce the risk of failure as an interconnect structure and improve the reliability of interconnection.
[0084] In some embodiments of the present application, the tensile strength of the nano-twinned copper layer prepared by electroplating the above composition is increased by greater than or equal to 25% compared with the ordinary copper layer, and the ductility is increased by greater than or equal to 40% compared with the ordinary copper layer. In some embodiments of the present application, the tensile strength of the nano-twinned copper layer prepared by electroplating the above composition is increased by greater than or equal to 30% compared with the ordinary copper layer, and the ductility is increased by greater than or equal to 50% compared with the ordinary copper layer.
[0085] In the embodiment of the present application, the transition layer thickness of the nano twinned copper layer prepared by electroplating the above composition is less than or equal to 1 μm. The transition layer is a transition state of the nano twinned accelerator in the process of inducing twin growth, and is a part of the nano twinned copper layer. A smaller transition layer thickness is conducive to obtaining an overall electroplated film layer with more uniform properties, so that the overall electroplated film layer has better performance.
[0086] In the implementation manner of the present application, a dimple section exists in the tensile section of the nano-twin copper layer prepared by electroplating the above-mentioned composition. A dimple section refers to a section of a dimple fracture (microporous aggregation type fracture) covered with a large number of microscopic pits. These micropits (pits) are called "dimples". Dimples are the main microscopic features of metal plastic fracture. It is a microscopic cavity produced by plastic deformation of the material within a micro-region, which is left on the section after nucleation, growth, aggregation and finally interconnection leading to fracture. The size of the dimple includes the average diameter and depth. Generally, when the fracture conditions are the same, the larger the dimple size, the better the plasticity of the material. The presence of a dimple section in the tensile section of the nano-twin copper layer in the implementation manner of the present application indicates that the nano-twin copper layer has good plasticity.
[0087] In some embodiments of the present application, the polyhydroxy polymer can be prepared in the following manner:
[0088] Potassium tert-butoxide is added into a reaction container, and under nitrogen protection, epoxy quaternary ammonium salt, solvent and 2,3-epoxypropanol are added into the reaction container, and the reaction is carried out at 130° C.-160° C. for 20-30 hours to obtain a polyhydroxy polymer.
[0089] The solvent may be, for example but not limited to, dimethyl sulfoxide.
[0090] The preparation of the above-mentioned polyhydroxy polymer is a hyperbranched reaction, and the hyperbranched reaction can control the N content in the molecular structure of the polyhydroxy polymer by the raw material feed ratio, and control the molecular weight of the polyhydroxy polymer by potassium tert-butoxide. Wherein, the polyhydroxy polymer is prepared by the reaction feed ratio of 2,3-epoxypropanol and epoxy quaternary ammonium salt is less than or equal to 500:1. In some embodiments, the reaction feed ratio of 2,3-epoxypropanol and epoxy quaternary ammonium salt can be 20-300:1. In some embodiments, the reaction feed ratio of 2,3-epoxypropanol and epoxy quaternary ammonium salt can be 50-200:1. In some embodiments, the reaction feed ratio of 2,3-epoxypropanol and epoxy quaternary ammonium salt can be 60-150:1. In some embodiments, the reaction feed ratio of 2,3-epoxypropanol and epoxy quaternary ammonium salt can be 80-120:1. The molecular weight of the polyhydroxy polymer can be 500g / mol-50000g / mol. The N content is the key to controlling the performance of the nanotwin structure. This reaction can simultaneously regulate the proportion and molecular weight of N, and the density of the nanotwin copper sheet layer can be controlled by adjusting the N proportion.
[0091] The present application also provides an application of the above-mentioned composition in the preparation of a metal layer by electroplating. The composition described in the embodiment of the present application can be used to prepare a dense nano-twinned copper layer with a high preferred (111) crystal plane orientation by electroplating, and the thickness of the transition layer is small, thereby greatly improving the mechanical properties and interconnection quality of the metal copper layer and improving the interconnection reliability. Nano-twinned copper has high strength and high conductivity, and can improve the interconnection reliability and performance in advanced packaging metal interconnection technologies such as ultra-fine RDL (ReDistribution Layer) and hybrid bonding.
[0092] In the embodiment of the present application, the electroplated metal includes the electroplated metal in the printed circuit board manufacturing process, the electroplated metal in the integrated circuit metal interconnection process, or the electroplated metal in the electronic packaging process. Specifically, the electroplated metal can be the electroplated metal in the process including through silicon via filling, substrate rewiring, metal bump deposition, via filling, etc.
[0093] In some embodiments of the present application, the electroplating preparation of the metal layer includes electroplating the metal layer in the conductive hole on the electronic substrate to achieve metal filling. The electronic substrate can be a common substrate, a printed circuit board, a packaging substrate, etc. The conductive hole can include a through hole, a blind hole, and a buried hole. It can be understood that the electroplating preparation of the metal layer can also be electroplating preparation of the metal layer on an electronic substrate of other structures.
[0094] In the embodiment of the present application, the metal layer can be any one of a copper layer, a copper alloy layer, a nickel layer, a nickel alloy layer, a tin layer, a tin alloy layer, a cobalt layer, a cobalt alloy layer, a ruthenium layer, a ruthenium alloy layer, a silver layer, and a silver alloy layer. The composition of the embodiment of the present application is applied to the electroplating preparation of the metal interconnect structure of the advanced packaging to improve the interconnect reliability.
[0095] The present application also provides a method for preparing a metal layer by electroplating, comprising the following steps:
[0096] The substrate to be electroplated is brought into contact with the composition described in the embodiment of the present application, and current is applied to the substrate to be electroplated for electroplating, so that a metal layer is formed on the substrate to be electroplated.
[0097] Specifically, the substrate to be electroplated may be immersed in the electroplating composition as a cathode, and the electroplating composition, i.e., the electroplating solution, as an electrolyte, together with a soluble or insoluble anode forms a conductive circuit, thereby achieving metal deposition on the substrate to be electroplated.
[0098] In the embodiments of the present application, there are no special restrictions on the structural size, shape, etc. of the substrate to be electroplated. In some embodiments of the present application, a via hole is provided on the substrate to be electroplated, and the metal layer includes an in-hole filling layer filling the via hole and a surface deposition layer deposited around the via hole. The via hole may include one or more of a through hole, a blind hole, and a buried hole. The via holes on the substrate to be electroplated may be completely the same or have different diameters and depths. In the embodiments of the present application, the diameter of the via hole 10 may be 10μm-200μm, and the depth may be 20μm-200μm.
[0099] In some embodiments of the present application, the process conditions of electroplating are: the electroplating temperature is 22°C-45°C, the current density is 0.1ASD-15ASD, and the electroplating time is 30min-300min. In some embodiments, the electroplating temperature is 22°C, 25°C, 30°C, 35°C, 40°C, 45°C, the current density is 0.1ASD, 0.2ASD, 0.5ASD, 1ASD, 1.5ASD, 2ASD, 2.5ASD, 3ASD, 4ASD, 5ASD, 8ASD, 10ASD, 12ASD, 15ASD, and the electroplating time is 30min, 60min, 90min, 120min, 150min, 180min, 200min, 250min, 300min. Under this process condition, it is conducive to electroplating to obtain a high-quality metal layer.
[0100] Generally, the via hole wall is metallized before electroplating, such as chemically plating a layer of metal on the via hole wall as a metal seed layer, for example, chemically plating a layer of copper seed layer on the via hole wall.
[0101] In the embodiment of the present application, after the metal layer is formed by electroplating, the metal layer may be planarized by using a process such as chemical mechanical planarization, and the surface deposition layer may be removed by planarization.
[0102] The method for preparing a metal layer by electroplating in the embodiment of the present application has a simple process and is easy to control.
[0103] See also Figure 2 The embodiment of the present application also provides an electronic substrate 100, including a base layer 101 and a metal layer 102 arranged on the base layer, and the metal layer 102 is formed by electroplating the composition described above in the embodiment of the present application, or is formed by the method for preparing a metal layer by electroplating described above in the embodiment of the present application.
[0104] In the embodiment of the present application, a via hole 10 is provided on the base layer 101, and the metal layer 102 includes an in-hole filling layer 1021 filling the via hole 10 and a surface deposition layer 1022 deposited around the via hole 10. A plurality of via holes 10 may be provided on the base layer 101, and the plurality of via holes 10 may have different diameters and depths, or may have the same diameter and depth. In the embodiment of the present application, the diameter of the via hole 10 may be 10 μm-200 μm, and the depth may be 20 μm-200 μm.
[0105] In the embodiment of the present application, a chemically plated metal seed layer 103 , such as a copper seed layer, formed by metallizing the via hole 10 is further included between the base layer 101 and the metal layer 102 .
[0106] The electronic substrate of the embodiment of the present application can be any substrate that needs to be electroplated to prepare a metal layer, and can be an amorphous substrate or a polycrystalline substrate. The structure, size, shape, etc. of the electronic substrate are not particularly limited. The electronic substrate can be, for example, a silicon substrate, a compound semiconductor substrate, an organic substrate, or a conductive metal substrate. The conductive metal substrate can be copper, aluminum, or any other conductive material.
[0107] The composition described above in the present application can be used to prepare a dense nano-twinned copper layer with a high preferred (111) crystal plane orientation by electroplating, and the thickness of the transition layer is small, thereby greatly improving the mechanical properties and interconnection quality of the metal copper layer and improving the interconnection reliability.
[0108] The embodiment of the present application also provides an electronic device, which uses the electronic substrate described in the embodiment of the present application. The electronic device may be a chip, a transistor, etc.
[0109] The embodiments of the present application are further described below with reference to a plurality of embodiments.
[0110] Example 1
[0111] Potassium tert-butoxide was placed in a reaction bottle, and nitrogen was introduced into the bottle under vacuum. Then trimethylglycidyl ammonium chloride and dimethyl sulfoxide were added into the reaction bottle. The temperature was raised to 60°C and stirred. Then 2,3-epoxypropanol was slowly injected into the reaction bottle. The temperature was further raised to 150°C and the reaction was carried out for 24 hours. After the reaction was completed, the solvent was removed by distillation under reduced pressure to obtain a polyhydroxy polymer. Figure 3 The NMR spectrum of the polyhydroxy polymer prepared in Example 1 is shown in FIG. Figure 3 In the experiment, the two peaks with chemical shifts of 3.34 and 3.64 correspond to H on the methyl group and H on the hydroxyl group of the product, respectively. The peak positions and area ratios are consistent with the theoretical values, proving that the polyhydroxy polymer was successfully synthesized.
[0112] The polyhydroxy polymer obtained in Example 1 was prepared into an electroplating solution, and the specific components of the electroplating solution were as follows: 200 g / L copper sulfate pentahydrate, 50 g / L sulfuric acid, 60 ppm chloride ion concentration, and 100 ppm polyhydroxy polymer.
[0113] A PVD Cu silicon substrate was used, the electroplating temperature was 25°C, and the current density was 5ASD for 40 minutes to electroplate a nano-twinned copper layer on the PVD Cu silicon substrate. Figure 4 This is a SEM image of the nano-twinned copper layer prepared in Example 1. Figure 4 It can be found that the transition layer thickness of the nano-twin copper on the polycrystalline substrate is extremely low, less than 1 μm, and the nano-twin copper layer grows in a columnar shape from bottom to top and is arranged in an orderly manner. Figure 5 The XRD pattern of the nano-twinned copper layer prepared in Example 1 is shown in FIG. Figure 5 It can be seen that the nano-twinned copper layer has an extremely high (111) crystal plane preferred orientation and basically no impurity peaks. Figure 6 The EBSD spectrum of the nano-twinned copper layer prepared in Example 1 is as follows: Figure 6 It can be seen that the microstructure of the nanotwinned copper layer is almost entirely copper crystals oriented in the (111) direction, which corroborates the results of XRD.
[0114] The nano-twinned copper layer prepared by the composition was subjected to a tensile test to measure its tensile strength and ductility. The test results are shown in Table 1. The tensile cross section was photographed by SEM. Figure 7 As shown, Figure 7 This is a SEM image of the tensile cross section of the nano-twinned copper layer prepared in Example 1. Figure 7 It can be seen that there is a dimple section in the tensile cross section of the nano-twin copper layer, and the dimple section is the key to improving the tensile strength and ductility.
[0115] Tensile test:
[0116] A 50um nano-twinned copper layer is plated on the surface of stainless steel, and then the nano-twinned copper layer is peeled off from the stainless steel surface. After peeling, thermal annealing is performed, and then the nano-twinned copper layer is prepared into a tensile sample using a dog-bone mold, and a tensile test is performed using a universal testing machine.
[0117] Comparative Example 1
[0118] The electroplating solution is prepared by using gelatin as a nano-twinning promoter. The specific components of the electroplating solution are as follows: 200 g / L copper sulfate pentahydrate, 50 g / L sulfuric acid, 60 ppm chloride ion concentration, and 100 ppm gelatin.
[0119] A PVD Cu silicon substrate was used, the electroplating temperature was 25°C, and the current density was 5ASD for 40 minutes to electroplate a nano-twinned copper layer on the PVD Cu silicon substrate. Figure 8 This is a cross-sectional SEM image of the nano-twinned copper layer prepared in Comparative Example 1. Figure 8 As shown, the thickness of the transition layer is ∼20 μm, the nano-twin coating is not dense, and the crystallization is relatively disordered.
[0120] The nano twinned copper layer prepared in Comparative Example 1 was subjected to a tensile test to measure its tensile strength and ductility. The tensile test operation was the same as that in Example 1. The test results are shown in Table 1.
[0121] Comparative Example 2
[0122] The electroplating solution of Comparative Example 2 differs from that of Example 1 only in that it does not contain a polyhydroxy polymer. The tensile test was performed to measure the tensile strength and ductility of the ordinary copper layer prepared by the electroplating solution of Comparative Example 2. The tensile test operation was the same as that of Example 1. The test results are shown in Table 1. The tensile cross section was photographed by SEM. Fig. 9 As shown, Fig. 9 is a SEM image of the tensile cross section of the ordinary polycrystalline copper layer of Comparative Example 2, Fig. 9 It can be seen that the polycrystalline copper in the ordinary copper layer only has a slip section, but no dimple section.
[0123] Table 1
[0124] Tensile strength(MPa) Ductility Example 1 Nano-twinned copper 383 12.9% Comparative Example 1 Nano-twinned copper 310 10.2% Comparative Example 2: Ordinary polycrystalline copper 295 8.64%
[0125] From the results in Table 1, it can be seen that the tensile strength and ductility of the nano-twinned copper layer of Example 1 of the present application are better than those of the nano-twinned copper layer of Comparative Example 1. Under the same conditions, compared with the ordinary polycrystalline copper layer of Comparative Example 2, the tensile strength of the nano-twinned copper layer of Example 1 of the present application is increased by about 30%, and the ductility is increased by about 50%. The nano-twinned copper layer of the embodiment of the present application has excellent mechanical properties and can improve the interconnection reliability.
[0126] Example 2 to Example 4
[0127] Polyhydroxy polymers with different feed ratios were used to prepare epoxy quaternary ammonium salt and 2,3-epoxypropanol, and the molecular weight of the product was controlled to be 45000 g / mol using a catalyst. The specific feed ratios are shown in Table 2. Based on different feed ratios, polyhydroxy polymers with different nitrogen contents were obtained in Examples 2 to 4, and the polyhydroxy polymers in Examples 2 to 4 were respectively prepared into electroplating solutions. The difference between the electroplating solutions in Examples 2 to 4 was only that different polyhydroxy polymers were used.
[0128] The method of Example 1 is used to electroplate a nano-twinned copper layer on a PVD Cu silicon substrate. Fig.10 is a cross-sectional SEM image of the nano-twinned copper layer of Example 2, Fig.11 This is a cross-sectional SEM image of the nano-twinned copper layer of Example 3. Fig.12 4 is a cross-sectional SEM image of the nano-twinned copper layer of Example 4. Figures 10 to 12 It can be seen that the transition layer thickness of the nano-twinned copper layer prepared in Examples 2 to 4 on the polycrystalline substrate is extremely low, and the nano-twinned copper layer grows in a columnar shape from bottom to top and is arranged in an orderly manner. The cross-sectional SEM of the nano-twinned copper layer in the examples with different feed ratios also shows that the nitrogen content has a great influence on the twin structure. The average thickness of the transition layer of the nano-twinned copper layer plated by the electroplating solution obtained in Examples 2 to 4 is statistically analyzed, and the results are shown in Table 2.
[0129] The nano-twinned copper layers prepared in Examples 2 to 4 were subjected to tensile tests to measure their tensile strength and ductility. The tensile test operation was the same as that in Example 1. The test results are shown in Table 2.
[0130] Table 2
[0131] Feed ratio Average thickness of transition layer / μm Tensile strength(MPa) Ductility Example 2 50:1 2.21 327 10.7% Example 3 100:1 1.57 379 12.4% Example 4 200:1 2.14 315 11.3%
[0132] From the experimental results in Table 2, it can be found that the thickness of the transition layer is greatly affected by the feed ratio, which is attributed to the fact that the N content of the polyhydroxy polymer is closely related to the thickness of the transition layer. From Table 2, it can also be seen that the nano-twinned copper layers obtained in Examples 2 to 4 have higher tensile strength and ductility, and the smaller the thickness of the transition layer, the higher the tensile strength and ductility of the nano-twinned copper layer.
[0133] It should be understood that the first, second and various numerical numbers involved in this document are only distinguished for the convenience of description and are not used to limit the scope of the present application.
[0134] In this application, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0135] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0136] In the present application, “-” represents a range value, including endpoint values at both ends. For example, the molecular weight of the polyhydroxy polymer is 500g / mol-50000g / mol, which means that the molecular weight of the polyhydroxy polymer is between 500g / mol and 50000g / mol, and includes the endpoint values 500g / mol and 50000g / mol.
[0137] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
Claims
1. A composition, characterized in that The composition comprises a metal ion source and a polyhydroxy polymer, wherein the polyhydroxy polymer is polymerized from monomer raw materials comprising epoxy quaternary ammonium salt and 2,3-epoxypropanol.
2. The composition according to claim 1, characterized in that The epoxy quaternary ammonium salt has the general structural formula shown in formula (1): In formula (1), n is an integer of 0≤n≤5, R1, R2 and R3 are independently selected from substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted n-propyl, substituted or unsubstituted isopropyl or derivatives thereof, and R4 is selected from H, substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted n-propyl, substituted or unsubstituted isopropyl or derivatives thereof.
3. The composition according to claim 1 or 2, characterized in that The epoxy quaternary ammonium salt includes one or more of trimethyl epoxypropyl quaternary ammonium salt, 3,4-epoxybutyl trimethyl quaternary ammonium salt, 4,5-epoxypentyl trimethyl quaternary ammonium salt, epoxyethyl triethyl quaternary ammonium salt, 2,3-epoxypropyl triethyl quaternary ammonium salt, 1,1-di(epoxypropyl) dimethyl quaternary ammonium salt, 2-methyl epoxypropyl trimethyl quaternary ammonium salt, 2-ethyl epoxypropyl trimethyl quaternary ammonium salt, 2-propyl epoxypropyl trimethyl quaternary ammonium salt, 2-methyl epoxyethyl trimethyl quaternary ammonium salt, and 2-methyl epoxyethyl triethyl quaternary ammonium salt.
4. The composition according to claim 1 or 2, characterized in that The polyhydroxy polymer is polymerized by the 2,3-epoxypropanol and the epoxy quaternary ammonium salt at a reaction feed ratio of less than or equal to 500:
1.
5. The composition according to any one of claims 1 to 4, characterized in that The molecular weight of the polyhydroxy polymer is 500 g / mol-50000 g / mol.
6. The composition according to any one of claims 1 to 5, characterized in that In the composition, the concentration of the polyhydroxy polymer is 0.01 ppm-5000 ppm.
7. The composition according to any one of claims 1 to 6, characterized in that The metal ion source includes any one of a copper ion source, a nickel ion source, a tin ion source, a cobalt ion source, a ruthenium ion source, and a silver ion source.
8. The composition according to claim 7, characterized in that The copper ion source includes one or more of copper sulfate pentahydrate and copper methane sulfonate; the concentration of the copper ion source in the composition is 1 g / L-300 g / L in terms of copper ions.
9. The composition according to any one of claims 1 to 8, characterized in that The composition further comprises at least one acid; the at least one acid comprises one or more of sulfuric acid and methanesulfonic acid; and the concentration of the at least one acid in the composition is 1 g / L-300 g / L.
10. The composition according to any one of claims 1 to 9, characterized in that The composition further comprises one or more of an accelerator, an inhibitor, a leveler, and an inorganic additive.
11. The composition according to claim 10, characterized in that The inorganic additive includes chloride ions, and the concentration of the chloride ions in the composition is 0.1 ppm to 100 ppm.
12. The composition according to claim 10 or 11, characterized in that The leveler comprises a copolymer of an ether and a nitrogen-containing compound; the concentration of the leveler in the composition is 0.01-100 ppm.
13. The composition according to any one of claims 10 to 12, characterized in that The accelerator comprises one or more of sodium 3-mercapto-1-propane sulfonate, sodium polydisulfide propane sulfonate and sodium N,N-dimethyl-dithiocarboxamide propane sulfonate; the concentration of the accelerator in the composition is 0.01ppm-500ppm.
14. The composition according to any one of claims 10 to 13, characterized in that The inhibitor comprises one or more of polyethylene glycol, polypropylene glycol, block copolymer PEO-PPO-PEO, block copolymer PPO-PEO-PPO, random copolymer of EO and PO, and propylene glycol block polyether; the concentration of the inhibitor in the composition is 1ppm-2000ppm.
15. The composition according to any one of claims 1 to 14, characterized in that The nano twinned copper layer prepared by electroplating the composition has a (111) crystal plane orientation.
16. The composition according to any one of claims 1 to 15, characterized in that The tensile strength of the nano-twinned copper layer prepared by electroplating the composition is increased by greater than or equal to 20% compared with the ordinary copper layer, and the ductility is increased by greater than or equal to 30% compared with the ordinary copper layer; wherein the ordinary copper layer is prepared under the same conditions by a plating solution to which the polyhydroxy polymer is not added compared with the composition.
17. The composition according to any one of claims 1 to 16, characterized in that The transition layer thickness of the nano twinned copper layer prepared by electroplating the composition is less than or equal to 1 μm; and a dimple section exists in the tensile section of the nano twinned copper layer.
18. Use of the composition according to any one of claims 1 to 17 in preparing a metal layer by electroplating.
19. The use according to claim 18, characterized in that The metal layer includes any one of a copper layer, a copper alloy layer, a nickel layer, a nickel alloy layer, a tin layer, a tin alloy layer, a cobalt layer, a cobalt alloy layer, a ruthenium layer, a ruthenium alloy layer, a silver layer, and a silver alloy layer.
20. The use according to claim 18 or 19, characterized in that The electroplating to prepare the metal layer includes electroplating the metal layer in the conducting hole on the electronic substrate to achieve metal filling.
21. A polyhydroxy polymer for preparing a metal layer by electroplating, characterized in that: The polyhydroxy polymer is polymerized from monomer raw materials including epoxy quaternary ammonium salt and 2,3-epoxypropanol.
22. The polyhydroxy polymer according to claim 21, characterized in that The epoxy quaternary ammonium salt has the general structural formula shown in formula (1): In formula (1), n is an integer of 0≤n≤5, R1, R2 and R3 are independently selected from substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted n-propyl, substituted or unsubstituted isopropyl or derivatives thereof, and R4 is selected from H, substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted n-propyl, substituted or unsubstituted isopropyl or derivatives thereof.
23. The polyhydroxy polymer according to claim 21 or 22, characterized in that The epoxy quaternary ammonium salt includes one or more of trimethyl epoxypropyl quaternary ammonium salt, 3,4-epoxybutyl trimethyl quaternary ammonium salt, 4,5-epoxypentyl trimethyl quaternary ammonium salt, epoxyethyl triethyl quaternary ammonium salt, 2,3-epoxypropyl triethyl quaternary ammonium salt, 1,1-di(epoxypropyl) dimethyl quaternary ammonium salt, 2-methyl epoxypropyl trimethyl quaternary ammonium salt, 2-ethyl epoxypropyl trimethyl quaternary ammonium salt, 2-propyl epoxypropyl trimethyl quaternary ammonium salt, 2-methyl epoxyethyl trimethyl quaternary ammonium salt, and 2-methyl epoxyethyl triethyl quaternary ammonium salt.
24. A method for preparing a metal layer by electroplating, characterized in that: The following steps are involved: The substrate to be electroplated is contacted with the composition according to any one of claims 1 to 17, and current is applied to the substrate to be electroplated for electroplating, so that a metal layer is formed on the substrate to be electroplated.
25. The method of claim 24, wherein: The substrate to be electroplated is provided with a via hole, and the metal layer includes an in-hole filling layer filling the via hole and a surface deposition layer deposited around the via hole.
26. The method according to claim 24 or 25, characterized in that The electroplating process conditions are: electroplating temperature is 22° C.-45° C., current density is 0.1ASD-15ASD, and electroplating time is 30min-300min.
27. An electronic substrate, characterized in that: It comprises a base layer and a metal layer arranged on the base layer, wherein the metal layer is formed by electroplating the composition according to any one of claims 1 to 17, or is formed by the method for preparing a metal layer by electroplating according to any one of claims 24 to 26.
28. An electronic device, characterized in that: The electronic device uses the electronic substrate according to claim 27.
